Local Viewer Preferences for Video Reaction Content About Indonesia by Creators on YouTube - Handoko, Libri Annisa Firdayasa; Rafi'ah, Kurnia Khafidatur (Universitas Airlangga, 2023)
Indonesia has about 127 million active YouTube users, equivalent to 21,42% of the platform's worldwide market share. This is certainly an ample opportunity for YouTube video creators to reach huge viewers of Indonesians. One of the content formats often used by creators to gain the attention of local audiences is the reaction content format. By reacting to viral content, it is easier to get exposure from viewers. This study aims to determine the local viewer preferences for reaction content influenced by the type of reacted content, video attributes of reaction content, self-impression of authentic videos that are given reactions, and the creator's characteristics and behavior. To support the research findings, 109 active students of FEB UNPAD in 2022/2023 were involved as respondents. Based on the descriptive and inferential analysis results executed by the software IBM SPSS Statistics 29.0., each independent variable positively impacts the viewer's interest in watching reaction content, proved by both t and F statistic significances.